From Gaming Elements to Purchase Intentions: The Influence of Perceived Enjoyment and Promotion Focus in Online Travel Bookings - Saidon, Janiffa; Hisham, Nur Aliah; Ahmad Atory, Nurul Ainun; Hashim, Hairulnizam; Johari, Mohd Hisham; Ahmad, Nur Syakirah; Sohid, Faizah Md; Ishak, Mohd Fikri (Information Management and Business Review, 2024)
This study examines the impact of gamification on purchase intentions in Malaysia’s online travel booking industry. As traditional platforms like Expedia face declining bookings due to economic challenges and the rise of competitors such as Airbnb, Agoda, and Booking.com, understanding the role of gamification in user engagement becomes crucial. The research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the effects of extrinsic and intrinsic gaming elements, perceived enjoyment, and promotional focus on purchase intention. A total of 141 respondents participated in the survey and the key findings reveal that extrinsic gaming elements, including points and rewards, have a significantly stronger impact on perceived enjoyment than intrinsic elements like membership levels. This heightened enjoyment, in turn, positively influences purchase intention. Additionally, the study finds that promotional focus moderates the relationship between perceived enjoyment and purchase intention, further enhancing the effect. The Importance-Performance Map Analysis (IPMA) indicates that while intrinsic gaming elements perform below average, they are less critical than other factors. Managers should prioritize improving aspects of high importance, but currently have, low performance to boost purchase intentions effectively. Overall, the research provides actionable insights for enhancing competitiveness in Malaysia’s digital travel marketplace, emphasizing the need for targeted gamification strategies to align with evolving consumer preferences. The findings offer a foundation for developing strategies that can help travel platforms maintain relevance and drive engagement in a competitive landscape.